Characterization and use of genetic variability of bank active germplasm Coffea canephora Pierre ex Froehner - Rocha, Rodrigo Barros; Santos, Diogo Vieira; Ramalho, André Rostand; Teixeira, Alexsandro Lara (Coffee Science - ISSN 1984-3909, 2014)
Efficient strategies to manipulate the genetic variability are crucial to the success of breeding programs Coffea canephora. Combinations between divergent parents express greater heterosis effect, and the selection of matrices consider both genetic divergence and superior agronomic performance. The objective of this study was to quantify the genetic diversity of C. canephora accesses Active Germplasm Bank of Embrapa Rondônia, in order to identify plants of greater genetic diversity and higher yield potential for hybridization. For this, between 1100 accessions were pre-selected 89 plants for evaluation of major components in the production of processed coffee. For quantification of genetic diversity technique for principal components associated landmarks to gather the information of genetic divergence and agricultural performance in a single analysis was used. The selected accessions showed significant genetic variability for the major components of production, highlighting the values of average blend above 17, which indicates a favorable condition for performing controlled crosses for selection of plants for increased productivity and grain size.